(untitled) (Journal of the College of Basic Education, 2022)
Many different societies have begun to apply the principle of education for all, which is the tendency towards the strategy of integrating disabled children with ordinary children in primary schools and those with simple levels, and as a way to achieve equality and balance as much as possible between the level of education and the needs of the disabled and the normal together.